Comparative Analysis of MONGODB and Oracle NOSQL: A Comparative Study of Oracle NoSQL and MongoDB Databases for Efficient Data Management (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Memory of Computer is its chief component. In today’s structure of things, majority of the intelligent machines have the required necessary hardware for the management of the data present and save it in a risk free manner to be retrieved later on. To coordinate these actions, database management systems work in coordination with the API’s at the lower level. To handle a variety of problems, a variety of data base management systems are there. In this paper I aim to provide an overview and a compare the Oracle NoSQL and MongoDB databases.